Novel insights into the hepatoprotective mechanisms of SGLT2 inhibitor empagliflozin in Zucker diabetic fatty rats - Comella, F.; Aragón-Herrera, A.; Melini, S.; Opallo, N.; Feijóo-Bandín, S.; Navatti, N. P.; Mattace Raso, G.; Gualillo, O.; Pirozzi, C.; Lago-Paz, F.; Meli, R. (Frontiers in Pharmacology, 2025)
The sodium-glucose cotransporter (SGLT)2 inhibitor empagliflozin (EMPA) is a hypoglycemic drug for patients with type 2 diabetes mellitus and cardiovascular disease. The mechanisms underlying the beneficial effects of EMPA in counteracting Metabolic Associated Fatty Liver Disease (MAFLD) are poorly understood. Our study aimed to evaluate the therapeutic mechanisms of EMPA treatment (30 mg/kg/day in drinking water for 6 weeks) on hepatic dysfunction observed in diabetic obese Zucker Diabetic Fatty (ZDF) rats. EMPA activated hepatic insulin signaling, increasing the phosphorylation of insulin receptor, AKT and AMP-activated protein kinase, and downregulated the expression of gluconeogenesis-related genes (glucose-6-phosphatase and phosphoenolpyruvate carboxykinase). In the liver of EMPA-treated rats, no difference in SGLT2 and SGLT1 expression was found, while a significant upregulation of GLUT2 protein levels suggested other converging mechanisms on hepatoprotective effects of EMPA. Moreover, EMPA improved hepatic lipid metabolism in ZDF rats, modulating key mediators of fatty acid metabolism and catabolism (cluster of differentiation 36, forkhead box protein O1, fatty acid binding protein 1) and mitochondrial function (uncoupling protein 2 and the mitochondrial transporter ATP-binding cassette 1). Then, we demonstrated EMPA effect against hepatic inflammation and fibrosis, associated with insulin resistance, and, for the first time, its potential as pro-resolving agent increasing immune cell recruitment along with the induction of resolvins (annexin A1 and IL-10). Taken together, our study provides new perspectives for EMPA as a multifaceted approach to counteract MAFLD in obesity and diabetes.